Combined Adjuvant of Poly I:C Improves Antitumor Effects of CAR-T Cells - Di, Shengmeng; Zhou, Min; Pan, Zeyan; Sun, Ruixin; Chen, Muhua; Jiang, Hua; Shi, Bizhi; Luo, Hong; Li, Zonghai (Frontiers in Oncology, 2019)
Chimeric antigen receptor modified T cells (CAR-T) therapy is an emerging immunotherapy against malignancies. However, only limited success was obtained in solid tumors. Polyinosinic-polycytidylic acid (poly I:C), ligand of TLR3, mediates innate immune and adaptive immune and shows broad antitumor effect on many types of cancer. In the present study, we combined EGFRvIII-targeted CAR-T cells with poly I:C treatment and evaluated the synergic antitumor effect in vitro and in immunocompetent mice bearing subcutaneous colon or orthotopic breast cancer xenografts. Poly I:C significantly promoted more IL-2 and IFN γ production as well as higher lytic activity of CAR-T cells. Upon systemic administration in vivo, CAR-T cells suppressed tumor growth obviously and poly I:C significantly enhanced the suppression. Further study showed that poly I:C exerts antitumor effect partially dependent on CD8 T cells and type I IFN signaling. In addition, poly I:C decreased MDSC quantity in peripheral blood and spleen and attenuated the immunosuppressive activity of MDSC on T cell proliferation and CAR-T cytolytic function. Depletion of MDSC with anti-Gr1 Ab further increased the antitumor effect of CAR-T cells plus poly I:C treatment. In conclusion, CAR-T treatment combined with intratumoral delivery of poly I:C resulted in synergistic antitumor activity. We thus provide a rationale to translate this immunotherapeutic strategy to solid tumors.